The Global Economic and Financial Impact of an Avian Flu Pandemic and the Role of the IMF. (Pamphlet Series; Pamphlet Series, No., 2006)
This paper, prepared by a working group of IMF staff, provides a preliminary assessment of the risks and potential impact to the global economy and financial system from a possible avian flu pandemic, discusses the IMF's role in helping member countries prepare their economic and financial systems for such a pandemic, and summarizes common elements of business continuity planning in the financial sector.